Quality of life of long-term survivors with Hodgkin lymphoma after high-dose chemotherapy, autologous stem cell transplantation, and conventional chemotherapy - Brandt, Juliane; Dietrich, Sascha; Meißner, Julia; Neben, Kai; Ho, Anthony Dick; Witzens-Harig, Mathias (Leukemia and lymphoma, 2010)
In this study, we investigated the quality of life (QoL) of long-term survivors with Hodgkin lymphoma who received high-dose chemotherapy (HDCT) followed by peripheral blood stem cell transplantation (PBSCT). QoL of this group was compared with QoL of patients who were treated with conventional chemotherapy and with QoL of the healthy German population. Two standardized questionnaires, the EORTC QLQ-C30 and the EQ-5D, including the visual analogue scale (VAS) were applied. A total of 98 patients were included in the study, all of them treated in our institution. Thirty-seven patients who received HDCT with PBSCT between 1986 and 2007 were compared with 61 patients treated with conventional chemotherapy and supplementary radiation between 1998 and 2009. The median follow-up for the HDCT group was 11 years. Statistical analysis with the one-sample t-test shows a reduced QoL of both groups of patients compared to the healthy population. Compared to the group of patients who received conventional chemotherapy, there is a tendency towards reduced QoL in patients with HDCT in all of the three main categories of the EORTC-QLQ-C30. However, these differences were not statistically significant, with the exception of the subcategory of dyspnoea, which was worse in the group that was treated with BCNU containing high-dose protocols. We conclude that the negative impact of both HDCT and conventional therapy on the QoL of long-term survivors with Hodgkin lymphoma should not be underestimated and should lead to the development of less toxic therapy strategies.
Gesehen am 08.02.2023